Result tracking-on-cloud: a development of mobile result management system / Ng Set Foong, Foo Fong Yeng and Chong Peng Hwa - Ng, Set Foong; Foo, Fong Yeng; Chong, Peng Hwa (Universiti Teknologi MARA, Perlis, 2020)
Assessment results are something private and confidential to most students. One may feel uncomfortable if his or her result is shown publicly. In most academic institutions, students’ results are displayed on a printed paper that contains the assessment of the whole class and the paper is usually posted on the notice board outside of the lecturer’s office. Students need to present personally at the lecturer’s office to check their results. Most of the time, students' names would be hidden on the paper but, students are still able to see each other’s results. Indirectly, the students’ results are not private though the lecturer does not intend to share them. In order to improve the privacy level of result management, a mobile application was programmed. This mobile application is an innovative tool that embedding the use of technology to assist students and educators in this era of Industrial Revolution 4.0. In this paper, the proposed mobile application/ app named as Result Tracking-on-Cloud (RTC) was presented. The users concluded that it is energy and time saving as they can check their results without present physically to the lecturer's office. At the same time, the privacy of students' result is secured.